Determinants of Performance of MSMEs in the Era of Industrial Revolution 4.0 in Medan City - Jantri Saragih; Romindo Megawati Pasaribu; Juara Simanjuntak; Herry D.S. Pasaribu; Vinsensius Matondang (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The existence of Micro, Small, and Medium Enterprises (MSMEs) is the largest part of the national economy, this is proven that MSMEs can be relied upon as a foundation in times of crisis such as the Covid-19 period. Constraints that are often experienced by MSME actors include establishing partnerships with third parties in terms of capital, making innovations in the face of market competition. The purpose of this study is to find out how business networks, product innovation, and business competition affect business performance for MSME actors in the city of Medan. This type of research is quantitative research by distributing questionnaires and observing MSME actors. The number of samples in this study was 94 business actors in the city of Medan. The results showed that the business network variable had an insignificant effect on the business performance variable. Product innovation and business competition variables have a significant influence on business performance. Viewed from R2, it shows that business networks, product innovation, and business competition are able to explain business performance by 37.8%.